Internally Generated Revenue (IGR) and the Economic Viability of States in Nigeria - Angahar, Jacob Sesugh; Olalere, Victor Dotun (Finance & Economics Review, 2023)
Purpose: The purpose of this study is to investigate Internally Generated Revenue (IGR) and the Economic Viability of States in Nigeria using State Government Debt Stock. Specifically, the study seeks to determine the effect of IGR on State government expenditure. Methods: Secondary data were used for this study. It used an annual panel data set spanning from 1986 to 2021 for six states each from Nigeria's six geopolitical zones. A Panel Vector Error Correction Model (PVECM) was used as the method of analysis. Results: Results showed that the IGR of States in Nigeria had a positive effect on State government expenditure. The Impulse Response Function of expenditure to shocks from IGR indicates that IGR for the periods under analysis positively affected State government expenditure, increasing their expenditure profile for the majority of the period under analysis. The result of the variance decomposition test of State government total debt stock (TDS) shows that IGR had the greatest shock on the total debt stock of State governments in the country after its own shock. The findings also revealed a mixed and varied outcome, demonstrating both a positive and negative influence of IGR on the overall debt stock of the state government. Implications: The study is expected to contribute to good economic management, such as managing the debt load at reasonable levels, as well as adequate economic planning backed by cost-effective expenditure. It will also contribute to the economic sustainability of Nigerian states. The uniqueness of this research is obvious in its ability to address the statewide problem of over-dependence on the federal government’s allocation.